Self‐fluorescent polymers for bioimaging. Issue 2 (23rd July 2021) - Ban, Qingfu; Li, Yan; Wu, Si
Abstract: Self‐fluorescent polymers with different fluorescent chromophores have attracted considerable attention in the field of fluorescence bioimaging due to their tunable topologies and compositions, which render high fluorescence intensity and multicolor photoluminescence. In this Review, recent advances into the construction of self‐fluorescent polymers via the integration of conventional fluorescent chromophores, such as fluorescent dyes and conjugated polymers, and nonconventional heteroatom‐containing chromophores are summarized. In addition, the classification and bonding modes of fluorescent chromophores in polymer backbones, fluorescence mechanisms, and multicolor photoluminescence are discussed. Finally, the promising applications of self‐fluorescent polymers for fluorescence bioimaging are highlighted. Abstract : Self‐fluorescent polymers with various topology can be flexibly constructed via the integration of conventional fluorescent chromophores, such as fluorescent dyes and conjugated polymers, and nonconventional heteroatom‐containing chromophores for fluorescence bioimaging.